Bench-to-bedside: Translational development landscape of biotechnology in healthcare - Caizhi Liao; Shadow Xiao; Xia Wang (Health Sciences Review, 2023)
Biotechnology is a rapidly evolving field that has the potential to transform the way we diagnose and treat diseases and is changing the landscape of healthcare. Great endeavors have been devoted to the field of healthcare biotechnology, and our knowledge of the subject has remarkably improved. By leveraging the latest advancements in molecular biology and genetics, new biotech paradigms are emerging, sparking new searches for novel solutions for human health and well-being. However, the clinical translational development of breakthrough biotechnology discoveries remains an intriguing challenge. Only a few biotech innovations have progressed to new transformative healthcare tools and therapies. In this review, we will outline the clinical translational development landscape of biotechnology in healthcare. Notable discoveries and translational developments in healthcare biotechnology, including classical discoveries and new paradigms, are thoroughly discussed. Even though great challenges remain in the bench-to-bedside translational development process, more groundbreaking biotech ideas are about to be translated into commercial products to bring positive health gains, with a tight multitude of collaboration among research institutes, healthcare providers, and industry partners.